State-of-the-Art Mini Review: Dual-Pathway Inhibition to Reduce Arterial and Venous Thromboembolism - Goldin, Mark; Koulas, Ioannis; Weitz, Jeffrey I; Spyropoulos, Alex C (Thrombosis and haemostasis, 2022)
Venous thromboembolism (VTE) and arterial thromboembolism (ATE) are linked by the common mechanism of thrombin generation. Historically these entities have been treated as separate pathophysiologic processes requiring different treatments: VTE, as the formation of fibrin-/coagulation-factor-derived thrombus in low-flow vasculature, requiring anticoagulants; versus ATE, as largely platelet-derived thrombus in high-flow vasculature, requiring antiplatelet agents. Observational studies have elucidated shared risk factors and comorbidities predisposing individuals with VTE to ATE, and vice versa, and have bolstered the strategy of dual-pathway inhibition (DPI)-the combination of low-dose anticoagulants with antiplatelet agents-to reduce thrombotic outcomes on both sides of the vasculature. Randomized clinical trials have evaluated the efficacy and safety of such regimens-mostly rivaroxaban and aspirin-in high-risk groups of patients, including those with recent acute or chronic coronary syndrome, as well as those with peripheral artery disease with or without revascularization. Studies of extended VTE prophylaxis in acutely ill medical patients have also contributed to the evidence evaluating DPI. The totality of available data supports the concept that DPI can reduce major and fatal thromboembolic outcomes, including stroke, myocardial infarction, VTE, and cardiovascular death in key patient cohorts, with acceptable risk of bleeding. Further data are needed to refine which patients derive the best net clinical benefit from such an approach. At the same time, other novel agents such as contact pathway inhibitors that reduce thrombin generation without affecting hemostasis-and thus maximize safety-should be assessed in appropriate populations.